The Effect of Valuing Social Responsibility by Combining the Company's Life Cycle - Nahid Bigmoradi; Ahmad Khodamipour; Omid pourheidari (Iranian Journal of Accounting, Auditing & Finance)
This research examines the effect of valuing social responsibility by combining the company's life cycle. In other words, by examining the role of life cycle stages on the relationship between high social responsibility and company value, the related literature on corporate social responsibility will be expanded to the less researched area in Iran. The statistical population of the research is the companies listed on the Tehran Stock Exchange. A sample of 115 companies from 2006 to 2021 is 1725 company-year. Multiple panel regression methods and STATA version 17 statistical software were used to test the hypotheses. The results show that although social responsibility and company value generally have a positive relationship, this relationship is conditional on the company's life cycle stages. The effect of each dimension of social responsibility on the company's value is different in the life cycle stages. Social responsibility's social and governance aspects predict higher firm value in all life cycle periods, but this effect is more significant in the decline period. The environmental aspect of social responsibility generally positively impacts the firm’s value, but this effect is insignificant at different life cycle stages.